Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Geografi - Juwita Amalda; Hermon Maurits Karwur; Muhamad Isa Ramadhan (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
This study seeks to ascertain how using the project-based learning approach affects bettering learning results. A non-equivalent control group design with a quasi-experiment is the technique employed. Independent Samples Test and N-Gain score analysis method. According to research, PjBL motivates students to do experiments, learn from experience, be creative, and learn new things. There was an impact of PjBL learning on learning outcomes, as evidenced by the tcount results of 4.121 with sig (2-tailed) 0.000 > 0.05 and a comparison of tcount values 4.121 > ttable 2.056. The PjBL learning paradigm significantly improves learning outcomes, with an N-Gain score of 67.31.